Archaeological, geomorphological and cartographical evidence of the sea level rise in the southern Levantine Basin in the 19th and 20th centuries. (10th July 2019) - Toker, E.; Sharvit, J.; Fischer, M.; Melzer, Y.; Potchter, O.
Abstract: Sea level variability affected by sea water mass is strongly associated with global, regional and local climate. In this context, the eastern Mediterranean Sea has been intensively investigated in recent decades because of its sensitivity to climatic and environmental variables, due to the influence of the Eastern Mediterranean Transient (EMT). The sea level in Israel during the Crusader period (12th-13th centuries CE) was found to be −0.5 ± 0.20 m relative to the present mean sea level (MSL). The difference between the Crusader sea level and the present-day MSL raises some questions which bring us to the aim of this study: estimating the timeline of the changes in sea level elevation in the eastern Mediterranean over the last two centuries. Archaeological evidence from areas of low tidal range, such as the Mediterranean Sea, can provide significant information on sea level changes for times when instrumental measurements where not yet available (e.g., before 1955 in Israel). The method employed in this study integrates two dimensions: The vertical—estimating the changes in sea levels relative to the present MSL, based on archaeological evidence; and the horizontal—determining the coastline changes, based on coastal architectural and geomorphological structures appearing in historical maps. Both the structural and the cartographic evidence for sea level changes date to the 19th Century, and indicate a rise of 0.36 m over the last two centuries. Findings attesting to horizontal changes, indicate a gradual migration of the coastline landward, to the east since 1863 and a rapid change in the coastal geomorphology at the beginning of the 20th century. The sea level increase from the 19th century might be, in part, a consequence of regional trends and, in part, a result of a gap between method accuracy (archaeology and modern measurements). Nevertheless, the drastic change in the geomorphology of the coastline may indicate an extreme meteorological event, such as a storm at sea, accompanied by a local rise of sea level, but further research is required to verify this.